PENGEMBANGAN SILABUS DAN RENCANA PELAKSANAAN PEMBELAJARAN AGAMA HINDU DI SMA - I Nengah Dugdug (Jurnal Santiaji Pendidikan (JSP), 2011)
The implementation of Hindu education in 1994 was still dominated by cognitive achievement rather than affective and psychomotor ability in learning objectives. In 2003 The National Education Department through National Education Standard Institution comprised national competency-based curriculum for Hindu subject. Competency-based Curriculum in Senior High School level needs further improvement through educational unit level curriculum because it will improve human sources quality especially teacher in developing syllabi and lesson plan. Based on the above fact, the writer formulates three problems as follows: (1) what are the steps of developing syllabus and lesson plan in Senior High School; (2) what are the factors that may affect the process of developing Hindu subject syllabus and lesson plan in Senior High School; (3) What efforts are needed in developing Hindu subject syllabus and lesson plan in Senior High School. The steps of developing Hindu subject syllabus and lesson plan can be independently or collaboratively in deliberation of subject teacher. The factors that encourage the development of the syllabus and lesson plan, that is, interest to the duties, responsibilities of the task, learning facilities, the attention of the head master, community demand and teachers’ administrative demand. These efforts which were done in developing syllabus and lesson plan was discussion, following seminar, workshop, and upgrading program as well as providing facilities and infrastructures. The Hindu Subject syllabus and lesson plan are expected to be applied in Senior High School.